Raise high the roof beam, carpenters ; and, Seymour, an introduction - Salinger, J. D. (Jerome David), 1919-2010.; Salinger, J. D., (Jerome David), 1919- (Boston : Little, Brown, and Co., 1991)
Two stories containing episodes from the life of the Glass family, with Seymour Glass, the oldest child, as the central character.
Wilson's Fiction.
Wilson's Senior High School.
Wilson's Fiction, March 2006.
Wilson's Senior High School, October 2007.
Young Adult
Keywords: Families -- Fiction; Family life -- Fiction